Command centers as cultural institutions: peacekeeping, knowledge production, and organizational meaning in Indonesia’s PMPP TNI - Suparman, Surya Wibawa; Armawi, Armaidy; Agussalim, Dafri; Triyana, Heribertus Jaka (Research Journal in Advanced Humanities, 2026)
This study examines the Command Center within Indonesia's Peacekeeping Mission Center of the Indonesian National Armed Forces (PMPP TNI) as a cultural and knowledge-producing institution that structures organizational memory, authority, and interpretive practices. Moving beyond conventional understandings of command centers as primarily operational or technological hubs, the study conceptualizes the Command Center as a regime of institutional knowledge through which dispersed information on personnel, logistics, training outcomes, and mission experiences is centralized, interpreted, and transformed into shared organizational meaning. It demonstrates that fragmented knowledge systems characterized by slow hierarchical reporting, incompatible databases, and episodic information flows have historically limited cumulative learning and institutional adaptation within PMPP TNI. It is based on a qualitative case study that analyzes institutional documents, operational reports, training evaluations, and organizational practices to examine this issue. The findings show that the Command Center consolidates epistemic authority by creating a cognitive and symbolic space where operational data and mission narratives converge, enabling pattern recognition, continuity, and the formalization of organizational memory. This institutionalization of knowledge supports cyclical feedback loops that shift the organization from reactive problem-solving toward anticipatory learning, while mediating hierarchical and relational forms of authority. Furthermore, the Command Center serves as a site of cultural governance, translating global peacekeeping norms into locally situated practices, fostering collective sensemaking, stabilizing institutional identity, and enhancing organizational resilience.